Phytates as a natural source for health promotion: a critical evaluation of clinical trials - Pires, Sonia M. G.; Reis, Rita Silva; Cardoso, Susana M.; Pezzani, Raffaele; Paredes-Osses, Esteban; Seilkhan, Ainur; Ydyrys, Alibek; Martorell, Miquel; Sönmez Gürer, Eda; Setzer, William N.; Abdull Razis, Ahmad Faizal; Modu, Babagana; et al. (Frontier, 2023)
Phytates are a type of organophosphorus compound produced in terrestrial ecosystems by plants. In plant feeds, phytic acid and its salt form, phytate, account for 60–80 of total phosphorus. Because phytate is a polyanionic molecule, it can chelate positively charged cations such as calcium, iron, and zinc. Due to its prevalence in vegetal tissues and the fact that people consume plants, phytate was first considered a potential health benefit. This updated review aims to summarize the current data on the results of clinical trials of phytates on human health, highlighting both beneficial and undesirable effects. To obtain these updated data, published papers in electronic databases such as PubMed/ MedLine, TRIP database, Wiley, Google Scholar, Baidu, and Scopus were searched. Study results have shown that phytate can have beneficial health effects such as antioxidant, anticancer potential and reduction of pathological calcifications in blood vessels and organs; but also, negative effects by reducing the absorption of minerals important for maintaining the homeostasis of the human body. According to these recent results derived from recent clinical studies, phytates may be a potential natural source for health benefits. To improve clinical efficacy and human health benefits, further dose-response studies are needed to determine effective therapeutic doses and potential interactions with conventional drugs.